Cellular and humoral immune responses in cats vaccinated with feline herpesvirus 1 modified live virus vaccine - Wu, Hongchao; Qiao, Peipei; Chen, Yunyu; Liu, Caihong; Huo, Ningning; Ding, Hangtian; Wang, Xiaojuan; Wang, Lulu; Xi, Xiangfeng; Liu, Yuxiu; Tian, Kegong (Frontiers in Veterinary Science, 2025)
Feline herpesvirus 1 (FHV-1) is an important pathogen causing infectious rhinotracheitis in felids, mainly infecting the upper respiratory tract and conjunctiva. Multiple vaccines are available to prevent FHV-1 infection, and the antibody levels are always used to evaluate their effectiveness. However, the cellular immunity response following immunization in cats remains unclear. This study investigated the immune responses (humoral and cellular) in cats immunized with the FHV-1 modified live virus vaccine. The results indicated that vaccination significantly reduced clinical signs, and antibody levels, including virus-neutralizing (VN) antibodies and immunoglobulin G (IgG), in the vaccine group were higher than those in the control groups. Additionally, the vaccine significantly increased cytokine secretion, indicating Th1-type cellular immune responses in cats. Moreover, cellular immune-related indicators, such as CD8+ T cells, CD4+ T cells, and interferon-gamma levels, were inversely correlated with clinical signs post-challenge by FHV-1 in vaccinated cats, highlighting its crucial role in protecting cats against FHV-1 infection. In summary, this study demonstrated the importance of cellular immune responses in protecting cats from FHV-1 infection after vaccination.